Enhancing immunogenicity by limiting susceptibility to lysosomal proteolysis - Delamarre, Lélia (The Rockefeller University Press, 2006)
T cells recognize protein antigens as short peptides processed and displayed by antigen-presenting cells. However, the mechanism of peptide selection is incompletely understood, and, consequently, the differences in the immunogenicity of protein antigens remain largely unpredictable and difficult to manipulate. In this paper we show that the susceptibility of protein antigens to lysosomal proteolysis plays an important role in determining immunogenicity in vivo. We compared the immunogenicity of proteins with the same sequence (same T cell epitopes) and structure (same B cell epitopes) but with different susceptibilities to lysosomal proteolysis. After immunizing mice with each of the proteins adsorbed onto aluminum hydroxide as adjuvant, we measured serum IgG responses as a physiological measure of the antigen's ability to be presented on major histocompatibility complex class II molecules and to prime CD4(+) T cells in vivo. For two unrelated model antigens (RNase and horseradish peroxidase), we found that only the less digestible forms were immunogenic, inducing far more efficient T cell priming and antibody responses. These findings suggest that stability to lysosomal proteolysis may be an important factor in determining immunogenicity, with potential implications for vaccine design.